2010
DOI: 10.2147/vhrm.s6668
|View full text |Cite
|
Sign up to set email alerts
|

Optimal use of β-blockers in high-risk hypertension: A guide to dosing equivalence

Abstract: Hypertension is the number one diagnosis made by primary care physicians, placing them in a unique position to prescribe the antihypertensive agent best suited to the individual patient. In individuals with diabetes mellitus, blood pressure (BP) levels >130/80 mmHg confer an even higher risk for cardiovascular and renal disease, and these patients will benefit from aggressive antihypertensive treatment using a combination of agents. β-blockers are playing an increasingly important role in the management of hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 80 publications
0
10
0
1
Order By: Relevance
“…Beta-blockers are also the most widely used class of medications in preventive migraine treatments and are reported to have favorable benefit-to-harm ratios ( Shamliyan et al, 2013 ). It is certainly possible that PCPs have a lot of knowledge of beta-blockers because they often prescribed beta-blockers to patients with hypertension ( McGill, 2010 ). Although it has not been determined whether PCPs intended to prescribe beta-blockers for both conditions, these medications have not been necessarily first-line medications for patients with only hypertension ( McGill, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Beta-blockers are also the most widely used class of medications in preventive migraine treatments and are reported to have favorable benefit-to-harm ratios ( Shamliyan et al, 2013 ). It is certainly possible that PCPs have a lot of knowledge of beta-blockers because they often prescribed beta-blockers to patients with hypertension ( McGill, 2010 ). Although it has not been determined whether PCPs intended to prescribe beta-blockers for both conditions, these medications have not been necessarily first-line medications for patients with only hypertension ( McGill, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is certainly possible that PCPs have a lot of knowledge of beta-blockers because they often prescribed beta-blockers to patients with hypertension ( McGill, 2010 ). Although it has not been determined whether PCPs intended to prescribe beta-blockers for both conditions, these medications have not been necessarily first-line medications for patients with only hypertension ( McGill, 2010 ). Thus, these medications may have been prescribed for patients with both migraine and hypertension, although most beta-blockers were consistently established as effective for patients only migraine with.…”
Section: Discussionmentioning
confidence: 99%
“…4 The most recent JNC guidelines (JNC7) recommend maintaining a target blood pressure (BP) of < 140/90 mm Hg in patients with hypertension to reduce heart disease risk. 7 It may first be useful first to briefly discuss the terminology used with medicine taking. This concept has undergone three key changes over the last few decades, recognized terminologically in the names "compliance", "adherence," and "concordance."…”
mentioning
confidence: 99%
“…13,16 It has been estimated that about 40% -60% of patients with hypertension are estimated to fail to adhere to the prescribed treatment. 7 Previous research showed that 50% of patients with hypertension stop their medication during a 12-month surveillance period and another 30% of patients underuse and accumulate their medicines. 17 A worldwide assessment by WHO has suggested that countries show a great variety with respect to their capacity for treating hypertension.…”
mentioning
confidence: 99%
“…Study showed that approximately 40–60% of the hypertensive patients failed to adhere to their prescribed medications . Besides, about 50% of the hypertensive patients stop their regimens during the first year of treatment and the other 30% of the patients underuse or accumulate their hypertensive medication . In the United States, poor adherence to antihypertensive treatment was estimated to cost 93.5 billion dollar of healthcare services, medications and missed days of work in 2010 .…”
Section: Introductionmentioning
confidence: 99%